Why Do Global Cities Engage with Global Climate Governance? The Case Studies of Shanghai and Chicago - Xu, Le (International Journal of Social Sciences and Public Administration, 2024)
As climate change intensifies, cities-particularly global cities-are emerging as critical players in addressing its challenges. Rising sea levels, extreme weather events, and other climate-related impacts threaten urban areas, compelling cities to take action. This article explores the motivations behind global cities’ engagement in global climate governance, focusing on both internal and external drivers. Using Chicago and Shanghai as case studies, the research investigates how cities’ roles as policy implementers, combined with the pursuit of political and economic gains, push them to the forefront of climate leadership. Externally, the inability of international negotiations to make significant progress, along with gaps in the global governance system, compels cities to intervene and address these shortcomings. By analyzing these dynamics, the paper highlights the growing importance of cities as influential actors in global climate governance and emphasizes their unique capacity to drive climate action.